Preparation method of environment-friendly degradable single-sided perspective paste

By using multi-layer composite structures and nanofilm technology, the problems of environmental friendliness, optical performance, and complex manufacturing processes of one-way vision film have been solved, achieving an environmentally friendly, stable, and durable one-way vision effect and extending its service life.

CN120963175AActive Publication Date: 2025-11-18DONGGUAN YIFAN MATERIAL TECH CO LTD

Patent Information

Application Number
CN202511185621.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-22
Publication Date
2025-11-18
Estimated Expiration
2045-08-22

AI Technical Summary

Technical Problem

Existing single-sided transparent films have problems such as insufficient environmental protection (e.g., slow degradation rate and release of microplastics), unstable optical performance (e.g., the transparency effect is greatly affected by light) and complex manufacturing process (e.g., high energy consumption of multi-layer co-extrusion and strict equipment requirements).

Method used

Employing a multilayer composite structure, including a mixture of polylactic acid, polybutylene succinate, and nano-montmorillonite, combined with fluorescent carbon nanodots, silver nanoparticles, and a fluorine-containing nanocoating, a nanofilm with a microporous array and a high-reflectivity coating is formed through melt blending, biaxial stretching, imprinting, and coating functionalization.

Benefits of technology

It achieves a comprehensive improvement in environmental friendliness, optical performance and durability. The material can be completely degraded in the natural environment, has excellent one-way vision effect and mechanical properties, and the preparation process has low energy consumption, thus extending its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120963175A_ABST
    Figure CN120963175A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an environment-friendly degradable single-sided perspective sticker, and belongs to the technical field of modified nano materials. The method comprises the following steps: (1) preparation of a multi-layer composite structure: mixing polylactic acid and poly (butylene succinate), adding nano-montmorillonite and a surface modifier, and carrying out melt blending to form a first-layer melt; stirring poly (butylene adipate-co-terephthalate) and fluorescent carbon nanodots to form a second layer of melt; the first layer, the pressure-sensitive adhesive layer and the second layer are co-extruded and compounded to form a film blank. And (2) construction of the nano-film: biaxially stretching the film blank, imprinting a micropore array, dipping in the silver nanoparticle suspension, and drying to obtain the nano-film. And (3) coating functionalization treatment: immersing into a fluorine-containing nano coating solution, and curing. And (4) post-treatment: carrying out secondary curing. The obtained single-sided perspective sticker is suitable for the fields of buildings, vehicle privacy films and the like, and solves the problems of serious pollution and slow degradation of a traditional sticker.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of modified nanomaterials technology, specifically, it relates to a method for preparing an environmentally friendly and biodegradable one-sided transparent film. Background Technology

[0002] Against the backdrop of increasing environmental awareness, significant progress has been made in materials science, particularly in the modification of polymer and nanomaterials. Traditional film materials, such as one-way vision films (also known as privacy films) used for windows, vehicles, or buildings, primarily rely on petroleum-based plastics such as polyethylene (PE), polyvinyl chloride (PVC), or polyester (PET). While providing visibility, these materials cause serious environmental pollution problems. According to relevant research, more than 300 million tons of plastic waste are generated globally each year, with non-degradable plastic films accounting for a considerable proportion, leading to long-term damage to soil and marine ecosystems. Therefore, research on environmentally friendly and biodegradable materials has become a hot topic, especially the application of biodegradable polymers such as polylactic acid (PLA), polybutylene succinate (PBS), and polybutylene terephthalate (PBAT). These materials are derived from renewable resources and can degrade into water and carbon dioxide in the natural environment.

[0003] The core function of one-way vision film is to achieve a one-way visual effect, meaning that external scenery is visible from one side, while the other side presents a mirror or opaque effect. This function is usually achieved through optical structure design, such as microporous arrays, nanoparticle coatings, or fluorescent materials to enhance contrast. As early as the 1990s, researchers began exploring the use of metal oxide thin films to manufacture one-way vision glass, but these materials often had poor durability and were not environmentally friendly. In the 21st century, with the rise of nanotechnology, modified nanomaterials have been introduced into film preparation, such as nano-montmorillonite (a layered silicate mineral) as a filler to enhance the mechanical properties and barrier properties of polymers. Polylactic acid (PLA), as a typical biodegradable polymer, is made from renewable resources such as corn starch, and its weight-average molecular weight is generally in the range of 120,000-180,000 g / mol, exhibiting good biocompatibility and degradability. The brittleness and low toughness of pure PLA limit its application in flexible films, so it is often blended with other polymers.

[0004] In the preparation of one-way vision films, multilayer composite structures of these biodegradable polymers have become a trend. However, in existing technologies, the light transmittance and one-way vision effect of these composite materials are often insufficient, requiring the introduction of functional additives such as fluorescent materials, which can emit fluorescence to enhance the contrast and visibility of the film. However, the dispersibility and stability of these materials still need to be optimized in existing methods. Existing one-way vision films still have several problems. First, they are not environmentally friendly: although many films claim to be biodegradable, the actual degradation rate is slow, taking months or even years in soil, and the degradation products may release microplastics. For example, traditional PLA-based films are easily hydrolyzed in humid environments, leading to a sharp decline in mechanical properties. Second, optical performance is unstable: the one-way vision effect is greatly affected by the angle of illumination and the environment, and fluorescent additives are easily quenched. Third, the manufacturing process is complex: multilayer co-extrusion and nano-construction processes are energy-intensive and require strict equipment, such as the difficulty in optimizing the parameters of twin-screw extruders, resulting in low yield and high cost. In practical applications, these problems manifest as easy peeling of the film during use, decreased vision effect, or environmental pollution. For example, automotive privacy films often lose their one-way function after 1-2 years of use, requiring frequent replacement and increasing waste. Architectural transparency films, on the other hand, face the problem of ultraviolet degradation, leading to color fading and optical failure. Summary of the Invention

[0005] To address the problems of insufficient environmental friendliness (such as slow degradation rate and release of microplastics), unstable optical performance (such as the transparency effect being greatly affected by light and the fluorescent additives being easily quenched) and complex manufacturing process (such as high energy consumption and strict equipment requirements for multi-layer co-extrusion) in existing technologies, the present invention adopts the following technical solution.

[0006] A method for preparing an environmentally friendly and biodegradable one-sided transparent film includes the following steps: (1) Preparation of a multilayer composite structure: First, mix 40-60 parts by weight of polylactic acid and 20-30 parts by weight of polybutylene succinate, add 10-20 parts by weight of nano-montmorillonite and 5-10 parts by weight of surface modifier and melt blend to form a first melt layer with a thickness of 100-200 μm; then take 15-25 parts by weight of polybutylene adipate terephthalate (CAS No. 55231-08-8) and 8-15 parts by weight of fluorescent carbon nanodots, stir and treat to form a second melt layer with a thickness of 50-100 μm; finally, through co-extrusion treatment, the above-mentioned first melt layer is formed. (1) A layer of melt, a pressure-sensitive adhesive layer with a thickness of 100-200μm and a mass fraction of 3-8 parts, and a second layer of melt are sequentially composited to form a multilayer composite film preform; (2) Construction of nanofilm: The film preform obtained in step (1) is biaxially stretched to form a preliminary film; then, an imprinting process is used to construct a micropore array; 4-10 parts of silver nanoparticle suspension are added for impregnation treatment, and after drying, a nanofilm is obtained; (3) Coating functionalization treatment: The nanofilm obtained in step (2) is immersed in a fluorine-containing nanocoating solution with a mass fraction of 6-12 parts, and then cured to obtain a coated nanofilm; (4) Post-treatment: The nanofilm obtained in step (3) is subjected to a second curing treatment.

[0007] Preferably, in step (1), the weight-average molecular weight of polylactic acid is 120,000-180,000 g / mol, and its CAS number is 26100-51-6; in step (1), the weight-average molecular weight of polybutylene succinate is 90,000-140,000 g / mol, and its CAS number is 25777-14-4; in step (1), the layer thickness of nano-montmorillonite is 1-5 nm, the interlayer spacing is 2-4 nm, and its CAS number is 1318-93-0; in step (1), the surface modifier is 3-aminopropyltriethoxysilane (CAS number 919-30-2), γ-methacryloyloxypropyltrimethoxysilane (CAS number 2530-85-0), isopropyl titanate (CAS number 546-68-9), or allyl glycidyl ether (CAS number 106-92-3).

[0008] Preferably, the equipment for melt blending in step (1) is a twin-screw extruder; the parameters for melt blending in step (1) are as follows: screw length-to-diameter ratio (42-48): 1, temperature 170-210℃, rotation speed 350-450r / min, time 25-35min; the weight-average molecular weight of polybutylene adipate terephthalate in step (1) is 130000-170000g / mol; the particle size of fluorescent carbon nanodots in step (1) is 3-8nm; the parameters for stirring in step (1) are as follows: stirring at 150-190℃ for 15-25min.

[0009] Preferably, the preparation method of fluorescent carbon nanodots in step (1) is as follows: Citric acid powder (CAS No. 77-92-9), polyethyleneimine (CAS No. 9002-98-6), guanidine hydrochloride (CAS No. 50-01-1), silicic acid (CAS No. 1343-98-2), and deionized water are mixed in a mass ratio of (10-20):(5-15):(2-4):(5-8):(100-150) and placed in a microwave reaction treatment with a power of 500 Ω. -800W, temperature 160-200℃, time 10-20min. After the reaction is completed, it is naturally cooled to room temperature to obtain the primary product. Then, 0.1-0.3 times the mass of the primary product of tannic acid (CAS No. 1401-55-4) is added, and the reaction is sealed at 120-160℃ for 4-8h to obtain the secondary product. Finally, 2-5 times the mass of the secondary product of ethanol is added for precipitation, and the mixture is centrifuged at 8000-12000r / min for 15-25min to obtain the final product.

[0010] Preferably, the parameters for co-extrusion treatment in step (1) are as follows: extrusion temperature 190-230℃, pressure 1-3MPa; the preparation method of the pressure-sensitive adhesive layer in step (1) is as follows: take 35-45% by mass of polyurethane emulsion (CAS No. 9009-54-5) with a weight average molecular weight of 60000-90000g / mol and chitosan powder with a molecular weight of 120000-180000g / mol and mix them at a mass ratio of 7:3, and the mixing speed is 400-600r. The mixture is stirred at a speed of 1000-1500 rpm for 40-50 minutes, then the pH is adjusted to 5-6. Next, 0.5-1 times the weight of chitosan powder in sodium glycerophosphate (CAS No. 1555-56-2) and 0.1-0.5 parts the weight of chitosan powder in polyoxyethylene ether (CAS No. 9002-93-1) are added. The mixture is then treated in an ice bath at a speed of 1000-1500 rpm for 20-25 minutes. The product is obtained by coating, where the curing temperature is 70-90℃ and the curing time is 1.5-2 hours.

[0011] Preferably, the parameters for biaxial stretching in step (2) are as follows: temperature 70-90℃, and stretching ratio of transverse to longitudinal is 2.5-3.5 times; the parameters for imprinting in step (2) are as follows: an array of nanocones with a period of 100-200nm and a depth of 80-120nm is imprinted on one side of the film preform, and laser perforation is performed on the other side of the film preform, wherein the pore diameter is 0.8-1.5mm and the porosity is 25-35%.

[0012] The parameters for the imprinting process in step (2) are as follows: Nanoimprinting technology is used on one side of the preform (usually the outer surface facing the brighter light) to construct an array structure of nanocones with a period of 100-200 nm and a depth of 80-120 nm. The aspect ratio of the nanocones is 0.8. Specifically, hot imprinting or UV imprinting equipment (such as a roller nanoimprinter, with a silicon-based or nickel-based template as the mold material) is used, and the imprinting temperature is controlled at 60-80℃ (to ensure that the polymer softens without degrading). The pressure is 0.5-2MPa, and the imprinting time is 5-15s / cycle. At the same time, laser drilling is performed on the other side of the film preform (the inner surface facing the darker side), with a hole diameter of 0.8-1.5mm and an opening rate of 25-35%. Laser drilling uses a CO2 laser or fiber laser (wavelength 1064nm, power 10-50W), a pulse frequency of 20-50kHz, and a scanning speed of 500-1000mm / s to form a uniformly distributed micropore array and avoid thermal damage.

[0013] Preferably, the parameters for the impregnation treatment in step (2) are as follows: the particle size of the silver nanoparticle suspension is 15-40 nm, the mass concentration is 0.3-0.8 wt%, the impregnation time is 10-20 min, and the impregnation temperature is 50-70 °C; the thickness of the nanofilm in step (2) is controlled at 100-140 μm.

[0014] Preferably, the parameters of the fluorine-containing nano-coating solution in step (3) are as follows: the solvent is ethanol, the solute is perfluoroalkylsilane, and the mass ratio between the solvent and the solute is 19:1. The perfluoroalkylsilane is heptadecafluorodecyltrimethoxysilane (CAS No. 83048-65-1), perfluorododecyltrichlorosilane (CAS No. 149213-65-0), or perfluorooctylethyltrichlorosilane (CAS No. 78560-44-8); the parameters of the immersion treatment in step (3) are as follows: temperature 45-65℃, time 8-20 min.

[0015] Preferably, the curing parameters in step (3) are as follows: vacuum degree 0.02-0.08MPa, temperature 90-110℃, and time 15-25min.

[0016] Preferably, the parameters for the secondary curing process in step (4) are as follows: under a nitrogen atmosphere, the temperature is 110-130℃, the pressure is 0.8-1.5MPa, and the time is 36-48h.

[0017] Compared to existing technologies, the beneficial effects of this invention are as follows: Through the synergistic design of material formulation, multilayer structure, and preparation process, this invention achieves a comprehensive improvement in environmental friendliness, optical performance, and durability. The mechanism is as follows: Excellent environmental protection and biodegradability enable greening throughout the entire life cycle. The basic materials of this invention are biodegradable polymers such as polylactic acid (PLA), polybutylene succinate (PBS), and polybutylene adipate terephthalate (PBAT). These materials are derived from renewable resources (such as corn starch) and can be ultimately decomposed into carbon dioxide and water by microorganisms in the natural environment (soil, compost), fundamentally solving the "white pollution" problem caused by traditional PVC and PET films. Furthermore, even the pressure-sensitive adhesive layer, as an adhesive, innovatively uses a polyurethane emulsion combined with biodegradable chitosan, ensuring the biodegradability consistency of the entire product (including the adhesive layer). The preparation process mainly uses melt blending and co-extrusion, significantly reducing the use of volatile organic compounds (VOCs), resulting in extremely low VOC emissions in the final product, meeting stringent indoor air quality standards. The superior optical performance and stable one-way vision effect are achieved through an optical structure based on a "micro-pore array + high-reflectivity coating." Structural basis: A micron-scale pore array (25-35% aperture ratio) constructed through laser drilling, combined with a double-sided imprinted nano-cone array, forms a unique optical surface. From the darker side (e.g., indoors), the human eye can observe the external scene through the micropores; while from the brighter side (e.g., outdoors), the human eye primarily receives light reflected by the silver nanoparticle coating, creating a mirror effect and thus achieving one-way vision. Enhanced effect: The innovation of this invention lies in the introduction of fluorescent carbon nanodots. These carbon dots are encapsulated in a second layer of melt (facing the dark side), absorbing some stray light (including ultraviolet light) from the environment and emitting visible fluorescence. This not only enhances the visual contrast and clarity on the dark side but also further amplifies the perception of the light intensity difference between indoors and outdoors. Even on cloudy days or at dusk with weak light contrast, a stable one-way vision effect is maintained, solving the problem of traditional vision stickers failing under specific lighting conditions. Excellent mechanical properties and long-lasting durability, with substrate reinforcement: Synergistic reinforcement is achieved by blending high-rigidity polylactic acid (PLA) with high-toughness polybutylene succinate (PBS) and introducing nano-montmorillonite treated with surface modifiers (such as silane coupling agents). The modified nano-montmorillonite can be uniformly dispersed in the polymer matrix in a lamellar form, forming a strong physical cross-linking network that effectively inhibits crack propagation, thereby significantly improving the tensile strength and toughness of the composite film and overcoming the brittleness of pure PLA. Surface protection: The final fluorinated nano-coating forms a dense, low-surface-energy protective layer on the film surface. Its superhydrophobic and oleophobic properties (similar to the lotus leaf effect) give the film excellent self-cleaning ability, making it less prone to dust and stain adhesion.Meanwhile, this coating effectively resists ultraviolet radiation, acid rain erosion, and physical scratches, delaying material aging, yellowing, and optical performance degradation, thus extending the service life of the film far beyond traditional products. Structural stability: The secondary curing process, conducted under specific temperature and pressure, fully releases the internal stress generated during stretching and imprinting, and strengthens the interfacial bonding between layers, ensuring dimensional stability of the film during long-term use, preventing edge curling, bubbling, or peeling. Attached Figure Description

[0018] Figure 1 This is a transmission electron microscope image of the fluorescent carbon nanodots prepared in Example 1.

[0019] Figure 2 The image shows the emission spectrum of the fluorescent carbon nanodots prepared in Example 1; line 1 is the emission spectrum after 30 minutes of UV excitation, and line 2 is the emission spectrum after 120 minutes of UV excitation. Detailed Implementation

[0020] The present invention will be described in detail below through specific embodiments. However, the uses and purposes of these illustrative embodiments are only for illustrating the invention and do not constitute any limitation on the actual scope of protection of the invention, nor are they intended to limit the scope of protection of the invention to these embodiments. For parameter ranges not mentioned, intermediate values ​​are selected. Also, for mass percentages or weight percentages not explicitly stated or mentioned, they generally refer to the final concentration after addition. Furthermore, in the present invention, the unit of mass parts is kilograms (Kg). It should be noted that the biodegradability mentioned in the present invention does not mean that all components achieve 100% degradation.

[0021] Example 1

[0022] Preparation of the multilayer composite structure: First, mix 50 parts by weight of polylactic acid (weight average molecular weight 150,000 g / mol) and 25 parts by weight of polybutylene succinate (weight average molecular weight 115,000 g / mol), add 15 parts by weight of nano-montmorillonite (layer thickness 3 nm, interlayer spacing 3 nm) and 7.5 parts by weight of surface modifier (γ-methacryloyloxypropyltrimethoxysilane), and melt blend using a twin-screw extruder with a screw length-to-diameter ratio of 45:1, a temperature of 190℃, a rotation speed of 400 r / min, and a time of 30 min to form a first melt layer with a thickness of 150 μm; then, take 20 parts by weight of polybutylene adipate terephthalate (weight average molecular weight 150,000 g / mol) and 11 parts by weight of... Five portions of fluorescent carbon nanodots (particle size 5.5 nm) were stirred at 170 °C for 20 min to form a second melt layer with a thickness of 75 μm. The preparation method of fluorescent carbon nanodots is as follows: Citric acid powder, polyethyleneimine, guanidine hydrochloride, silicic acid, and deionized water were mixed in a mass ratio of 15:10:3:6.5:125 and subjected to microwave reaction treatment at a power of 650 W, a temperature of 180 °C, and a time of 15 min. After the reaction, the mixture was allowed to cool naturally to room temperature to obtain the primary product. Then, 0.2 times the mass of the primary product was added to tannic acid, and the mixture was sealed and reacted at 140 °C for 6 h to obtain the secondary product. Finally, 3.5 times the mass of the secondary product was added to precipitate the product, and the mixture was centrifuged at 10000 r / min for 20 min to obtain the final product. The transmission electron microscope image of the fluorescent carbon nanodots is shown below. Figure 1 As shown, the fluorescence spectrum is as follows: Figure 2 As shown; finally, the first melt layer, 5.5 parts by weight of a 150μm thick pressure-sensitive adhesive layer, and the second melt layer are sequentially compounded by co-extrusion to form a multi-layer composite film preform; the extrusion temperature of the co-extrusion process is 210℃ and the pressure is 2MPa; the preparation method of the pressure-sensitive adhesive layer is as follows: 40% by weight of polyurethane emulsion (weight average molecular weight of 75000g / mol) and chitosan powder (molecular weight of 150000g / mol) are mixed at a mass ratio of 7:3, the mixing speed is 500r / min, the mixing time is 45min, then the pH is adjusted to 5.5, then 0.75 times the mass of chitosan powder sodium glycerophosphate and 0.3 times the mass of chitosan powder polyoxyethylene ether are added, and the mixture is treated at 1250r / min for 22.5min under ice bath conditions, and then coated with a coating process, wherein the curing temperature of the coating is 80℃ and the curing time is 1.75h to obtain the product.

[0023] Construction of nanofilms: The obtained film preform was biaxially stretched to form a preliminary film. The biaxial stretching parameters were 80℃ temperature and a stretching ratio of 3:1. Then, an imprinting process was used to construct a microporous array. A nanocone array with a period of 150nm and a depth of 100nm was imprinted on one side of the film preform, while laser drilling was performed on the other side of the film preform, with a pore diameter of 1.15mm and an open area of ​​30%. Seven parts by weight of silver nanoparticle suspension were added for impregnation treatment. The silver nanoparticle suspension had a particle size of 27.5nm and a mass concentration of 0.55wt%. The impregnation time was 15min and the impregnation temperature was 60℃. After drying, the nanofilm was obtained. The thickness of the nanofilm was controlled at 120μm.

[0024] Coating functionalization treatment: The obtained nanofilm was immersed in a fluorine-containing nanocoating solution with a mass ratio of 9 parts. The solvent of the fluorine-containing nanocoating solution was ethanol, and the solute was heptadecafluorodecyltrimethoxysilane. The immersion treatment temperature was 55℃ and the time was 14 min. Then, a curing treatment was performed with a vacuum degree of 0.05 MPa, a temperature of 100℃, and a time of 20 min to obtain the coated nanofilm.

[0025] Post-treatment: The obtained nanofilm was subjected to a secondary curing treatment; under a nitrogen atmosphere, the temperature was 120℃, the pressure was 1.15MPa, and the time was 42h.

[0026] The resulting environmentally friendly and biodegradable one-sided transparent film has the following physical parameters: a thickness of 120μm and good one-sided transparent effect.

[0027] The specific parameters for Examples 2-12 and Comparative Examples 1-16 are listed in the following tables. The tables are designed according to the progress of the steps, and each table reflects different parameter values ​​for the Examples / Comparative Examples, covering all endpoint values ​​and intermediate values.

[0028] Table 1: Parameters of Multilayer Composite Structures

[0029]

[0030] First, Table 1 has a clear and concise structure, containing seven columns: number (Examples 1-6), polylactic acid (g, weight-average molecular weight g / mol), polybutylene succinate (g, weight-average molecular weight g / mol), nano-montmorillonite (g, layer thickness nm, interlayer spacing nm), surface modifier (g, type), first melt layer thickness (μm), and melt blending parameters (temperature °C, rotation speed r / min, time min, screw L / D ratio). These columns correspond to the core components and processing conditions of the first melt layer. Polylactic acid (PLA) and polybutylene succinate (PBS) serve as the main biodegradable polymer substrates, providing the material's toughness and biodegradability; nano-montmorillonite acts as a filler to enhance mechanical properties; surface modifiers improve the dispersibility of nanomaterials; melt thickness controls the uniformity of the layer structure; and melt blending parameters ensure the efficiency and uniformity of the mixing process. The entire table is arranged by example, showcasing a gradual design of parameters for easy comparison and optimization.

[0031] In terms of its role in the overall invention, Table 1 forms the core foundation for the preparation of the multilayer composite structure, directly influencing subsequent steps such as co-extrusion, stretching, and coating. The first melt layer acts as a support layer, forming a physical cross-linking network through the layered structure of nano-montmorillonite, enhancing tensile strength and crack resistance. Surface modifiers promote uniform dispersion of nanoparticles, prevent agglomeration, and improve optical transparency and degradation uniformity. Optimization of these parameters ensures the final single-sided transparent film's environmental performance (e.g., degradation rate > 50%), optical effects (e.g., transparency > 90%), and mechanical durability (e.g., elongation > 200%). Compared with the comparative example, the parameter ranges in Table 1 avoid performance degradation (e.g., strength reduction of 20-30%) caused by missing additives or exceeding the range, demonstrating the invention's innovation and practicality. In summary, Table 1 is not only a summary of experimental data but also a manifestation of the inventors' scientific design to achieve synergistic material enhancement, laying a solid foundation for subsequent nanofilm construction and functionalization, and promoting the advancement of environmentally friendly and biodegradable film technology.

[0032] Table 2: Parameters of Multilayer Composite Structures

[0033]

[0034] Table 2 has the same structure as Table 1, containing seven columns: number (Comparative Examples 1-8), polylactic acid (g, weight-average molecular weight g / mol), polybutylene succinate (g, weight-average molecular weight g / mol), nano-montmorillonite (g, layer thickness nm, interlayer spacing nm), surface modifier (g, type), first melt layer thickness (μm), and melt blending parameters (temperature °C, rotation speed r / min, time min, screw L / D ratio). These columns focus on the variation experiments of the first melt layer, with many parameters fixed at the baseline values ​​of Example 1 (e.g., polylactic acid 50g, 150000g / mol, etc.) to highlight the influence of changes in a single variable. The design of Table 2 reflects the principles of scientific experimentation, revealing the synergistic effect of nano-montmorillonite, surface modifier, and processing parameters through a control group, avoiding blind optimization, and ensuring the rationality of the inventive parameter range (e.g., polylactic acid 40-60g, temperature 170-210 °C).

[0035] Table 2 systematically covers three types of parameter deviations: omissions, substitutions, and range deviations. Omissions (e.g., Comparative Examples 1 and 2) directly weaken the enhancement mechanism; substitutions (e.g., Comparative Example 3) test the effectiveness of non-optimal materials; and range deviations (e.g., below / above) reveal the importance of boundary conditions. For example, when the polymer molecular weight and amount added are outside the scope of the invention (e.g., Comparative Examples 4 and 8), the balance between toughness and strength is disrupted; processing temperatures below the range (e.g., Comparative Example 5) may lead to uneven mixing, while excessive addition (e.g., Comparative Examples 6 and 7) increases costs and may cause side reactions. These deviations are not random but are targeted at the core elements of the invention, reflecting the rigor of the experiment.

[0036] Table 3: Parameters of Multilayer Composite Structures

[0037]

[0038] Table 3 has the same structure as Tables 1 and 2, and contains 7 columns: number (Examples 7-12), polylactic acid (g, weight-average molecular weight g / mol), polybutylene succinate (g, weight-average molecular weight g / mol), nano-montmorillonite (g, layer thickness nm, interlayer spacing nm), surface modifier (g, type), first layer melt thickness (μm), and melt blending parameters (temperature °C, rotation speed r / min, time min, screw length-to-diameter ratio).

[0039] These columns focus on fine-tuning the first layer of melt, with many parameters expressed in decimals (e.g., 52.5 g), reflecting the precision of the experiment and the gradient design. Compared to the integer values ​​in Table 1, Table 3 places greater emphasis on intermediate values, which helps reveal the sensitivity of parameter variations to performance, such as how small fluctuations in molecular weight affect the material's toughness and degradation rate.

[0040] From the perspective of parameter patterns, Table 3 shows a fine gradient design: the mass fractions of polylactic acid and polybutylene succinate fluctuate within the ranges of 42.5-57.5g and 21.25-28.75g, respectively, and the weight-average molecular weight changes accordingly from 127,500-172,500g / mol and 95,000-132,500g / mol. These decimal adjustments reflect the continuity of parameters and avoid the integer jumps in Table 1.

[0041] The amount of nano-montmorillonite added is 11.25-18.75g, the layer thickness is 1.5-4.5nm, and the interlayer spacing is 2.25-3.75nm, all within the scope of the invention, ensuring uniform dispersion of the layered structure. 5.5-9.25g of surface modifiers are used, with a variety of types (titanium esters, ethers, silanes), highlighting the adaptability of different modifiers. The thickness of the first layer gradually changes from 112.5-187.5μm to match thickness-sensitive applications.

[0042] The melt blending parameters—temperature 175-205℃, rotation speed 362.5-437.5 r / min, time 26.25-33.75 min, and aspect ratio 42.5-47.5:1—are all within the high-efficiency range. These regular variations are not arbitrary but based on the invention mechanism: the intermediate values ​​optimize the melt flowability of the polymer and the exfoliation effect of the nanofiller, reducing energy consumption and improving environmental friendliness.

[0043] Table 3 illustrates the further optimization of parameters, directly supporting the functional design of the first melt layer. These examples validate the flexibility of the material formulation: high molecular weight PLA enhances rigidity, low temperature and rotational speed control ensure consistent degradation, and the diversity of modifiers adapts to different nano-montmorillonite specifications. These parameters ensure the smooth progress of subsequent steps (such as co-extrusion and stretching) and contribute to the environmental advantages of the final product.

[0044] Table 4: Parameters of Multilayer Composite Structures

[0045]

[0046] Table 4 details the key material ratios, molecular weights, nano-additive specifications, surface modifier types, melt thicknesses, and melt blending processing parameters for the preparation of the first melt layer in Comparative Examples 9 to 16. This table is a continuation of Table 2 (Comparative Examples 1-8) and contrasts sharply with Tables 1 and 3 (Examples 1-12). It further verifies the necessity and boundary conditions of the invention parameters by introducing variations with parameters below or exceeding the scope of the invention. In the preparation method of the environmentally friendly biodegradable one-sided transparent film, the first melt layer, as the base layer of the multi-layer composite structure, directly affects the mechanical strength, optical properties, and degradation efficiency of the material through parameter optimization. The parameter design in Table 4 focuses on extreme deviation scenarios, such as excessive polymer, excessively high temperatures, or inappropriate thicknesses, aiming to reveal potential defects and thus enhance the superiority of the examples and the robustness of the method. These comparative examples not only highlight the scientific validity of the invention's scope (e.g., polylactic acid 40-60g, temperature 170-210℃, thickness 100-200μm) but also provide risk warnings for practical applications.

[0047] Table 4 systematically expands the types of deviations based on parameter deviation patterns: deviations below the range (e.g., Comparative Examples 9, 13, 14, 15) may lead to functional deficiencies, such as uneven mixing or weakened reinforcement; deviations above the range (e.g., Comparative Examples 10, 11, 12, 16) cause over-problems, such as accelerated degradation or material inhomogeneity. These patterns cover polymer ratios (Comparative Examples 11, 12), additive dosages (Comparative Examples 13, 14), processing parameters (Comparative Examples 9, 10), and structural dimensions (Comparative Examples 15, 16), reflecting a comprehensive risk assessment. Compared to the omissions and substitutions in Table 2, Table 4 focuses more on quantifying boundaries, revealing the sensitive ranges of parameters. For example, temperatures exceeding 210℃ may increase VOC emissions, while thicknesses below 100μm are prone to tensile fracture.

[0048] Table 5: Parameters of Multilayer Composite Structures

[0049]

[0050] Table 5 details the key material ratios, specifications, thicknesses, and processing parameters for the preparation of the second melt layer, pressure-sensitive adhesive layer, and co-extrusion process in Examples 1-6 and Comparative Examples 1-8. This table emphasizes the parameter design of the optical reinforcement layer (based on polybutylene terephthalate (PBAT) and fluorescent carbon nanodots) and the pressure-sensitive adhesive layer in the second layer. In the preparation method of the environmentally friendly biodegradable one-sided transparent film, the second layer provides fluorescence and optical modulation, while the co-extrusion step achieves multilayer composite, ensuring the one-sided transparency and adhesion of the product. The parameter settings in Table 5 are intended to be combined with the first layer deviations in the previous table to evaluate the overall performance impact.

[0051] Table 5 illustrates the gradient design of the embodiments based on parameter patterns: PBAT mass fraction 15-25g, weight-average molecular weight 130,000-170,000g / mol; fluorescent carbon nanodots 8-15g, particle size 3-8nm. These ranges ensure the biodegradability and fluorescence stability of the second layer (e.g., particle size 5-6nm optimizes light scattering). The second layer thickness gradually varies from 50-100μm to match optical requirements; stirring parameters are 150-190℃ temperature and 15-25min time, emphasizing gentle treatment to avoid nanodot aggregation. Pressure-sensitive adhesive layer 3-8g, thickness 100-200μm, works synergistically with co-extrusion temperature 190-230℃ and pressure 1-3MPa to achieve low-pressure, high-efficiency composite. The "zero variation" principle of the comparative examples highlights the control principle: when the second layer is fixed, deviations in the first layer (such as omissions or out-of-range values ​​in Tables 2 and 4) will amplify overall defects, such as reducing transparency or increasing the risk of peeling. This design reflects the modularity of the experiment and avoids interference from multiple variables.

[0052] Table 6: Parameters of Multilayer Composite Structures

[0053]

[0054] First, the structure of Table 6 is consistent with that of Table 5, containing a total of 7 columns: number (Examples 7-12, Comparative Examples 9-16), polybutylene adipate terephthalate (g, weight-average molecular weight g / mol), fluorescent carbon nanodots (g, particle size nm), second layer melt thickness (μm), stirring parameters (temperature °C, time min), pressure-sensitive adhesive layer (g, thickness μm), and co-extrusion parameters (temperature °C, pressure MPa). These columns focus on the stirring and mixing of the second layer and multilayer co-extrusion, complementing the parameters of the first layer in the previous table.

[0055] Table 7: Parameters of Multilayer Composite Structures

[0056]

[0057] Table 7 outlines the nanodot synthesis process, comprising seven columns: Number (Examples 1-6, Comparative Examples 1-8), Citric Acid Powder (g): Polyethyleneimine (g): Guanidine Hydrochloride (g): Silicate (g): Deionized Water (g), Microwave Parameters (Power W, Temperature °C, Time min), Tannic Acid Ratio (times), Sealed Reaction (Temperature °C, Time h), Ethanol Ratio (times), Centrifugation (r / min, Time min). These columns cover the entire process, including raw material mixing, microwave-assisted heating, tannic acid addition (possibly as a stabilizer), sealed reaction, ethanol washing, and centrifugal purification, complementing the parameters in the second layer of the previous table. Notably, the parameters for Comparative Examples 1-8 are identical, reflecting the modularity of the experimental design: maintaining a constant nanodot synthesis to isolate the influence of upstream (first layer) or downstream (co-extrusion) variations.

[0058] Table 7 illustrates the gradient design of the examples based on parameter patterns: the raw material ratios are 10-20g citric acid, 5-15g polyethyleneimine, 2-4g guanidine hydrochloride, 5-8g silicic acid, and 100-150g deionized water. These ranges ensure the green synthesis and uniform particle size of the nanodots (corresponding to 3-8nm in Tables 5 / 6). Microwave parameters were gradually varied: power 500-800W, temperature 160-200℃, and time 10-20min, emphasizing efficient heating to promote carbonization. Tannins were added at 0.1-0.3 times the normal concentration, and a sealed reaction at 120-160℃ for 4-8h optimized the crosslinking process. Washing with 2-5 times the normal concentration in ethanol and centrifugation at 8000-12000r / min for 15-25min ensured purification efficiency.

[0059] Table 8: Parameters of Multilayer Composite Structures

[0060]

[0061] Table 8 illustrates the fine-grained gradient design of the examples based on parameter patterns: the raw material ratios, such as citric acid (11.25-18.75 g) and polyethyleneimine (6.25-13.75 g), with decimal variations covering the middle range, ensure the quantum yield and biocompatibility of the nanodots. Microwave parameters, gradually varying from 537.5-762.5 W, 165-195 °C, and 11.25-18.75 min, optimize carbonization efficiency; tannins (0.125-0.275 times), sealed at 125-155 °C, and for 4.5-7.5 h, emphasize process stabilization. Ethanol (2.375-4.625 times) and centrifugation (8500-11500 r / min, 16.25-23.75 min) ensure purification. The deviation patterns of the comparison ratio highlight negative tests: missing / excessive / insufficient (e.g., 900W > 800W upper limit, 10min < 15min lower limit), simulate synthesis failure scenarios, and amplify defects such as low yield or uneven particle size.

[0062] Table 9: Parameters of Multilayer Composite Structures

[0063]

[0064] Table 10: Parameters of Multilayer Composite Structures

[0065]

[0066] Tables 9 and 10 together detail the key material ratios, mixing conditions, pH adjustments, additive ratios, and processing and coating parameters in the preparation of pressure-sensitive adhesive layers or coating layers for Examples 1-12 and Comparative Examples 1-16. These tables mark the transition from the previous tables (Tables 7-8, focusing on the synthesis of fluorescent carbon nanodots) to adhesive layer or coating processes, emphasizing biocompatible blends based on polyurethane emulsions and chitosan powder, supplemented with sodium glycerophosphate and polyoxyethylene ether as stabilizers and surfactants. In the preparation method of environmentally friendly biodegradable one-way transparent films, this layer provides adhesion and surface protection, directly affecting interlayer interface stability and overall degradation performance. The design of Tables 9 (Examples 1-6, Comparative Examples 1-8) and 10 (Examples 7-12, Comparative Examples 9-16) reflects the inventors' exploration of parameter continuity: the examples use gradient variations (e.g., 35-45% polyurethane emulsion, molecular weight 60,000-90,000 g / mol) to cover integer and decimal ranges, while the comparative examples are fixed in Table 9, and deviations (e.g., below range, missing) are introduced in Table 10, aiming to combine with the second layer in Table 6 and the nanodots in Table 8 to evaluate the effect of adhesive layer deviations on optical and adhesive properties.

[0067] From the parameter patterns, Tables 9 and 10 together demonstrate the gradient design of the examples: 35-45% polyurethane emulsion with a molecular weight of 60,000-90,000 g / mol, and 120,000-180,000 g / mol of chitosan. These ranges ensure the flexibility and degradability of the adhesive layer (e.g., the high molecular weight of chitosan enhances biocompatibility). Mixing parameters are gradually varied from 400-600 rpm to 40-50 min, with pH 5-6 optimizing acidity; additive ratios of 0.5-1 times sodium glycerophosphate and 0.1-0.5 times polyoxyethylene ether emphasize stability. Treatment is performed at 1000-1500 rpm for 20-25 min, and coating is carried out at 70-90°C for 1.5-2 h to ensure uniform coating. The "zero variation" pattern of the comparative examples in Table 9 is similar to that in Table 7, while the deviations in Table 10 (e.g., 30% < 35% lower limit, missing values) are similar to those in Table 8, highlighting negative impacts such as low adhesion or instability. This design reflects the continuity from integer gradients (Table 9) to fractional finesse and boundary testing (Table 10).

[0068] Table 11: Parameters of Nanofilms

[0069]

[0070] Table 11 details the key process parameters for the preparation of nanofilms in Examples 1-12 and Comparative Examples 1-16, including biaxial stretching, imprinting, laser perforation, silver nanoparticle deposition, and film thickness control. This table marks the transition from the previous tables (Tables 9-10, focusing on adhesive coating) to nanoscale optical processing, emphasizing film forming based on biaxial stretching, combined with imprinted textures, perforated ventilation, and silver nanoparticles to enhance reflectivity / fluorescence properties. In the preparation method of environmentally friendly biodegradable one-sided transparent films, the nanofilm layer provides one-sided light transmission and optical selectivity, directly affecting transparency, breathability, and durability. The examples use gradient variations (e.g., stretching temperature 70-90°C, stretching ratio 2.5-3.5 times) covering integer and decimal ranges, while Comparative Examples 1-9 are kept constant, and Comparative Examples 10-16 introduce deviations (e.g., below / above range, missing values), aiming to evaluate the impact of nanoprocessing deviations on overall optical and mechanical properties in conjunction with the adhesive layers in Table 10 and the nanodots in Table 8. This not only validates the rationality of the nanofilm parameter range (such as thickness 100-140μm and silver particle size 15-40nm), but also highlights that if the processing is not optimized, it may reduce the clarity of the view or increase the uneven degradation.

[0071] Table 12: Parameters for Coating Functionalization Treatment

[0072]

[0073] Table 12 details the key materials and process parameters used in the coating functionalization process of Examples 1-12 and Comparative Examples 1-16, including the amount and type of fluorinated nano-coating solution, immersion conditions, and vacuum curing parameters. This table marks a continuation from the previous table (Table 11, focusing on nanofilm processing) to surface functionalization, emphasizing the application of fluorinated silane-based nano-coatings that achieve waterproof, anti-fouling, and self-cleaning properties through immersion and curing. In the preparation method of environmentally friendly biodegradable one-way transparent films, this coating provides surface protection and directly affects the product's weather resistance, transparency durability, and biodegradability compatibility. The examples employed gradient variations (e.g., solution volume 6-12g, immersion temperature 45-65℃) covering both integer and decimal ranges, and cycled through three types of fluorinated silanes (heptadecyltrimethoxysilane, perfluorododecyltrichlorosilane, and perfluorooctylethyltrichlorosilane). Comparative Examples 1-9 remained constant, while Comparative Examples 10-16 introduced deviations (e.g., missing, substitution, exceeding / below the range). This was intended to be combined with the film parameters in Table 11 and the adhesive layer in Table 10 to evaluate the impact of coating deviations on overall optical and protective performance.

[0074] From the perspective of parameter patterns, Table 12 shows the gradient design of the embodiments: the amount of fluorine-containing solution is 6-12g, and the solute is cyclical with three kinds of fluorinated silanes to ensure the waterproof synergy of different chain lengths; the immersion temperature is gradually changed from 45-65℃ and the time is 8-20min to optimize the adhesion efficiency; the curing vacuum degree is 0.02-0.08MPa, the temperature is 90-110℃, and the time is 15-25min to emphasize uniform curing.

[0075] Table 13: Post-processing parameters

[0076] serial number Secondary curing parameters (temperature °C, pressure MPa, time h) Example 1 120,1.15,42 Example 2 110,0.8,36 Example 3 130,1.5,48 Example 4 115,0.975,39 Example 5 125,1.325,45 Example 6 120,1.15,42 Example 7 120,1.15,42 Example 8 122.5,1.2375,43.5 Example 9 117.5,1.0625,40.5 Example 10 127.5,1.4125,46.5 Example 11 112.5,0.8875,37.5 Example 12 125,1.325,45 Comparative Example 1 120,1.15,42 Comparative Example 2 120,1.15,42 Comparative Example 3 120,1.15,42 Comparative Example 4 120,1.15,42 Comparative Example 5 120,1.15,42 Comparative Example 6 120,1.15,42 Comparative Example 7 120,1.15,42 Comparative Example 8 120,1.15,42 Comparative Example 9 120,1.15,42 Comparative Example 10 120,1.15,42 Comparative Example 11 120,1.15,42 Comparative Example 12 120,1.15,42 Comparative Example 13 100 (below range), 1.15, 42 Comparative Example 14 120, 0.5 (below range), 42 Comparative Example 15 120, 1.15, 30 (below range) Comparative Example 16 140 (out of range), 1.15, 42

[0077] From the perspective of parameter patterns, Table 13 shows the gradient design of the embodiment: temperature gradually changes from 110 to 130°C, pressure from 0.8 to 1.5 MPa, and time from 36 to 48 hours to ensure the controllability of the curing process.

[0078] To verify the performance of the environmentally friendly and biodegradable one-sided transparent film described in this invention, multi-dimensional tests were conducted on the products prepared in Examples 1-12 and Comparative Examples 1-16. The tests included optical properties (one-sided transmittance and visible light transmittance), mechanical properties (tensile strength and elongation at break), biodegradability (degradation rate in the natural environment), environmental performance (VOC emissions), and durability (transparency attenuation rate after UV aging). All test data were based on actual material properties (e.g., one-sided transmittance of 80-95% is considered excellent; degradation rate exceeding 50% within 3-6 months in the natural environment is considered biodegradable; VOC < 50 mg / m³). 3 (For environmental protection purposes) The testing methods are as follows: Optical performance test: A spectrophotometer (model: Lambda950, PerkinElmer) was used to measure the single-sided transmittance (the clarity of external objects observed from the perspective side, calculated as transmittance of the perspective side / reflectance of the non-perspective side × 100%) and visible light transmittance (average value of wavelength 380-780nm). Sample size: 10cm × 10cm, thickness measured uniformly. Mechanical performance test: According to GB / T528-2009 standard, a universal testing machine (model: Instron5567) was used to test the tensile strength (MPa) and elongation at break (%). Samples were strip-shaped, and the testing speed was 50mm / min. Degradability test: According to GB / T19276.1-2003 standard, the sample was buried in simulated natural soil (temperature 25℃, humidity 60%), and the mass loss rate (%) was measured after 90 days. The degradation rate was calculated as (initial mass - remaining mass) / initial mass × 100%. Environmental performance testing: VOC emissions (mg / m³) were measured using a gas chromatography-mass spectrometry (GC-MS) system (model: Agilent 7890B) in accordance with GB30981-2020 standard. 3The sample was placed in a sealed chamber and sampled after 24 hours. Durability test: According to GB / T16422.2-2014 standard, the sample was irradiated with a UV aging chamber (model: QUV / se, Q-Lab) for 1000 hours, and then the single-sided transmittance was measured. The attenuation rate was calculated as (initial transmittance - transmittance after aging) / initial transmittance × 100%.

[0079] Table 14: Test Results of Optical and Mechanical Properties

[0080]

[0081] Based on the data patterns, Table 14 shows a clear binary distribution: the first 6 rows (low value group) have a VOC range of 11.9-13.2 mg / m³. 3 (average 12.4 mg / m²) 3 The emissions decreased by 4.6-5.1% (average 4.8%), with minimal fluctuations, demonstrating the low emissions and high stability achieved through gradient optimization in the implementation example; the last 8 rows (high-value group) showed VOCs ranging from 64.1-67.4 mg / m³. 3 (average 65.6 mg / m²) 3 The degradation rate was 17.8-19.2% (average 18.4%), with slightly large fluctuations, highlighting the high environmental burden and rapid optical degradation caused by comparative deviations (such as parameters below / beyond the range). The two indicators were positively correlated (high VOC accompanied by high degradation), following a pattern similar to the performance comparison in the previous table. This emphasizes that optimized parameters (such as 110-130℃ curing in Table 13) can control VOCs within environmental thresholds, while deviations (such as low-temperature curing) amplify emissions and aging. Regarding the correlation with the previous tables, Table 14 is a downstream validation of Table 13 (post-processing parameters) and Table 12 (coating functionalization), directly quantifying the overall process effect and forming a closed-loop system with the nanofilm parameters in Table 11. The low-value group corresponds to the gradient of the embodiments (such as 112.5-127.5℃ in Table 13, matching low attenuation), ensuring synergy between coating and curing (e.g., fluorine coating reduces VOCs); the high-value group corresponds to deviations in the comparative examples (such as the high emissions caused by the low temperature of 100℃ in Comparative Example 13 in Table 13), amplifying negative cascading effects (e.g., coating defects amplify UV attenuation). For example, tests show that the overall performance of the embodiments is 5-6 times better than that of the comparative examples, proving that parameter optimization (such as immersion at 45-65℃ in Table 12) directly reduces VOCs and maintains transmittance >95%, while deviation cascading effects lead to environmental unfriendliness, further highlighting the necessity of parameters throughout the entire process.

[0082] Table 15: Results of Optical and Mechanical Performance Tests (Part 2)

[0083]

[0084] Based on the data patterns, Table 15 shows a similar binary distribution to Table 14, but with slightly expanded values: the first 6 rows (low value group) have a VOC range of 11.7-13.1 mg / m³. 3 (average 12.2 mg / m²) 3 The emissions decreased by 4.4-5.2% (average 4.8%), with minimal fluctuations, demonstrating the low emissions and high stability achieved through gradient optimization in the implementation example; the last 8 rows (high-value group) showed VOCs ranging from 63.9-68.1 mg / m³. 3 (average 66.2 mg / m²) 3 The attenuation was 17.7-19.4% (average 18.7%), with slightly larger fluctuations, highlighting the high environmental burden and rapid optical degradation caused by comparative deviations (such as parameters below / above the range). The two indicators were positively correlated (high VOC accompanied by high attenuation), with a pattern similar to Table 14, but the peak value of the high-value group was higher, emphasizing that optimized parameters (such as 110-130℃ curing in Table 13) can control VOC within the environmental protection threshold, while deviations (such as low-temperature curing) further amplify emissions and aging, showing the repeatability of the experiment.

[0085] In summary, the test results show that the one-sided transmittance of the products in the examples ranges from 91.8% to 93.2%, the degradation rate from 54.7% to 56.2%, and the VOC from 11.7% to 13.2 mg / m³. 3 The comparative sample exhibits excellent performance; however, due to component deficiency or parameter deviation, its performance significantly declines (e.g., transmittance drops to 76.8-79.3%, VOC increases to 63.9-68.1 mg / m³). 3 This demonstrates the superiority of the preparation method of the present invention.

[0086] The above description, in conjunction with specific embodiments, provides a further detailed explanation of the present invention. It should not be construed that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art, several simple deductions or substitutions can be made without departing from the concept of the present invention, and all such deductions or substitutions should be considered to fall within the scope of protection defined by the claims submitted herein.

Claims

1. A method for preparing an environmentally degradable single-sided see-through sticker, characterized in that: The method comprises the following steps: (1) Preparation of the multi-layer composite structure: first, 40-60 parts by mass of polylactic acid and 20-30 parts by mass of polybutylene succinate are mixed, 10-20 parts by mass of nano-montmorillonite and 5-10 parts by mass of a surface modifier are added, and melt blending is performed to form a first layer melt with a thickness of 100-200 μm; then, 15-25 parts by mass of polybutylene adipate terephthalate and 8-15 parts by mass of fluorescent carbon nanodots are stirred to form a second layer melt with a thickness of 50-100 μm; finally, the first layer melt, 3-8 parts by mass of a pressure-sensitive adhesive layer with a thickness of 100-200 μm, and the second layer melt are sequentially combined by co-extrusion to form a film blank of the multi-layer composite structure; (2) Construction of the nano-film: the film blank obtained in step (1) is subjected to biaxial stretching to form a preliminary film; then, a micro-hole array is constructed by using a stamping process; (3) Functionalization treatment of the coating layer: the nano-film obtained in step (2) is immersed in 6-12 parts by mass of a fluorine-containing nano-coating solution for soaking treatment, and then solidification treatment is performed to obtain the nano-film after the coating layer treatment; and (4) Post-treatment: the nano-film obtained in step (3) is subjected to secondary solidification treatment. In step (1), the weight-average molecular weight of the polylactic acid is 120,000-180,000 g / mol; in step (1), the weight-average molecular weight of the polybutylene succinate is 90,000-140,000 g / mol; in step (1), the layer thickness of the nano-montmorillonite is 1-5 nm, and the interlayer spacing is 2-4 nm; and in step (1), the surface modifier is 3-aminopropyl triethoxysilane, γ-methacryloyloxypropyl trimethoxysilane, isopropyl titanate, or allyl glycidyl ether.

2. The method for preparing the environmentally friendly biodegradable one-sided transparent film according to claim 1, characterized in that: In step (1), the device for melt blending is a double-screw extruder; in step (1), the parameters for melt blending are as follows: screw length-diameter ratio (42-48): 1, temperature: 170-210 ℃, rotation speed: 350-450 r / min, and time: 25-35 min; in step (1), the weight-average molecular weight of the polybutylene adipate terephthalate is 130,000-170,000 g / mol; in step (1), the particle size of the fluorescent carbon nanodots is 3-8 nm; and in step (1), the parameters for stirring are as follows: stirring at 150-190 ℃ for 15-25 min.

3. The method for preparing the environmentally friendly biodegradable one-sided transparent film according to claim 1, characterized in that: ​ 4. The method of claim 1, wherein the method further comprises: The preparation method of the fluorescent carbon nanodots in step (1) is as follows: citric acid powder, polyethyleneimine, guanidine hydrochloride, silicic acid and deionized water are mixed according to the mass ratio (10-20):(5-15):(2-4):(5-8):(100-150), placed in a microwave reaction treatment, wherein the power is 500-800W, the temperature is 160-200℃, and the time is 10-20min, after the reaction is completed, it is naturally cooled to room temperature to obtain a primary product, then 0.1-0.3 times the mass of the primary product of tannic acid is added, and sealed reaction is carried out at 120-160℃ for 4-8h to obtain a secondary product, and finally 2-5 times the mass of the secondary product of ethanol is added for precipitation, centrifuged at 8000-12000r / min for 15-25min to obtain the final product.

5. The method of claim 1, wherein the method further comprises: The parameters of the co-extrusion treatment in step (1) are as follows: extrusion temperature 190-230℃, pressure 1-3MPa; the preparation method of the pressure-sensitive adhesive layer in step (1) is as follows: polyurethane emulsion with a mass percentage of 35-45% and a weight average molecular weight of 60000-90000g / mol is mixed with chitosan powder with a molecular weight of 120000-180000g / mol according to a mass ratio of 7:3, the mixing speed is 400-600r / min, and the mixing time is 40-50min, then the pH is adjusted to 5-6, then 0.5-1 times the mass of glycerol sodium phosphate of the chitosan powder and 0.1-0.5 parts of polyoxyethylene ether of the chitosan powder are added, and treated at a speed of 1000-1500r / min under ice bath conditions for 20-25min, and the product is obtained by coating process, wherein the coating solidification temperature is 70-90℃, and the solidification time is 1.5-2h.

6. The method of claim 1, wherein the method further comprises: The parameters of the biaxial stretching in step (2) are as follows: temperature 70-90℃, transverse and longitudinal stretching ratio 2.5-3.5 times; the parameters of the embossing treatment in step (2) are as follows: nano-cone arrays with a period of 100-200nm and a depth of 80-120nm are embossed on one side surface of the film blank, and at the same time, laser holes with a diameter of 0.8-1.5mm and an opening rate of 25-35% are punched on the other side of the film blank.

7. The method of claim 1, wherein the method further comprises: The parameters of the immersion treatment in step (2) are as follows: the particle size of the silver nanoparticle suspension is 15-40nm, the mass concentration is 0.3-0.8wt%, the immersion time is 10-20min, and the immersion temperature is 50-70℃; the thickness of the nanometer film in step (2) is controlled to be 100-140μm.

8. The method of claim 1, wherein the method further comprises: The parameters of the fluorine-containing nanometer coating solution in step (3) are as follows: the solvent is ethanol, the solute is perfluoroalkylsilane, and the mass ratio between the solvent and the solute is 19:1, wherein the perfluoroalkylsilane is heptadecafluorodecyltrimethoxysilane, perfluorododecyltrichlorosilane or perfluorooctylethyltrichlorosilane; the parameters of the soaking treatment in step (3) are as follows: temperature 45-65℃, time 8-20min.

9. The method of claim 1, wherein the method further comprises: The parameters of the solidification treatment in step (3) are as follows: vacuum degree 0.02-0.08MPa, temperature 90-110℃, time 15-25min.

10. The method of claim 1, wherein the method further comprises: The parameters of the secondary curing treatment in step (4) are as follows: temperature 110-130℃, pressure 0.8-1.5MPa, time 36-48h under nitrogen atmosphere.

Citation Information

Patent Citations

  • Biodegradable oriented composite film with high gas barrier property

    CN112250899A

  • Nanoscale biodegradable composite material as well as preparation method and application thereof

    CN116082780A

  • Heat-insulating anti-ultraviolet one-way perspective film and preparation method thereof

    CN119017802A

  • Biodegradable nanocomposite composition comprising a blend of polyactic acid and polybutylene succinate

    KR1020100125644A

  • Low birefringence light control film and methods of making

    US20090115943A1

Cited By

  • Polyvinyl chitosan and tannic acid composite active membrane as well as preparation method and application thereof

    CN122011473A

  • Polyvinyl chitosan tannic acid composite active film, preparation method thereof and application thereof

    CN122011473B